Register in Ensemble Stars Music Game - Uflih, Mifta Ramdani; Arvian, Elsan; Noryatin, Yeni (Sekolah Tinggi Bahasa Asing JIA, 2024)
This research aims to describe the linguistic form, discover the meaning, and identify the register's function in the Ensemble Stars Music game. The theories applied are Finegan's theory to describe register linguistic forms, Halliday's theory to find register meaning, and identify register functions. This study uses a qualitative methodology by way of discourse analysis. The data taken is in the form of words related to gameplay. From the 25 data found, there are 14 single words, 7 compound words, and 4 shortenings divided into 3 initialisms and 1 acronym. Regarding the meaning discovered, most registers are classified as open variations compared to closed ones. Based on the analysis, the register function that appears the most is personal. In addition, the registers also have imaginative, representational, interactional, and instrumental functions.